2009
DOI: 10.1007/s10162-009-0163-1
|View full text |Cite
|
Sign up to set email alerts
|

Human Medial Olivocochlear Reflex: Effects as Functions of Contralateral, Ipsilateral, and Bilateral Elicitor Bandwidths

Abstract: Animal studies have led to the view that the acoustic medial olivocochlear (MOC) efferent reflex provides sharply tuned frequency-specific feedback that inhibits cochlear amplification. To determine if MOC activation is indeed narrow band, we measured the MOC effects in humans elicited by 60-dB sound pressure level (SPL) contralateral, ipsilateral, and bilateral noise bands as a function of noise bandwidth from 1/2 to 6.7 octaves. MOC effects were quantified by the change in stimulus frequency otoacoustic emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
100
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 49 publications
12
100
5
1
Order By: Relevance
“…The tuning of the efferent effect filter (0.5-0.7 octaves above and below the signal frequency) is within the range obtained in humans using OAEs (Lilaonitkul and Guinan 2009;Zhao and Dhar 2012). 4.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The tuning of the efferent effect filter (0.5-0.7 octaves above and below the signal frequency) is within the range obtained in humans using OAEs (Lilaonitkul and Guinan 2009;Zhao and Dhar 2012). 4.…”
Section: Discussionsupporting
confidence: 67%
“…The frequency range of the efferent effect found in the present study is similar to that observed with the measurement of otoacoustic emissions in humans, using simultaneous or contralateral elicitors. The tuning of the efferent effect can extend 0.5-2 octaves above and below the frequency range of interest (spontaneous OAEs) or probe frequency (stimulus-frequency OAEs), as measured using simultaneous ipsilateral/contralateral tones (Lilaonitkul and Guinan 2009;Zhao and Dhar 2012). In most cases the tone/narrowband noise eliciting the efferent effect has maximal effect above a presentation level of 60 dB SPL, and in some cases the efferent effect has been shown to be more pronounced if the elicitor/precursor sound is about 0.5-1 octave below the probe frequency (e.g., Mott et al 1989;Harrison and Burns 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Even if it did, its effects would be identical for PTCs obtained with and without CWN and would cancel out in the comparison [this is unless the effects of ipsiand contralateral MOCR elicitors add up nonlinearly, which is unlikely the case as suggested by Fig. 3C of Lilaonitkul and Guinan (2009a)]. Therefore, the present approach may still be reasonably used to characterize the effect of contralateral sounds on cochlear responses.…”
Section: Discussionmentioning
confidence: 84%
“…Electrical shocks on the midline olivo-cochlear bundle may have activated both the ipsi-and contralateral MOCR, hence exaggerating the effects. A further piece of evidence in support of contralateral MOCR effects at 4 kHz is that Lilaonitkul and Guinan (2009a) showed that contralateral broadband noise reduced the level of human SFOAE both at 500 Hz and 4 kHz. The magnitude of the reduction was about 2.4 times larger at 500 Hz than at 4 kHz (e.g., their Fig.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the ipsilateral noise may have (1) elicited the ipsilateral MOCR, (2) produced an excitatory response in AN fibers, which decreased the change in discharge rate in response to the tone, and (3) suppressed the tone. Although several studies have separated the elicitor from the signal either in time or in frequency in order to be able to compare ipsilateral and contralateral effects Maison and Liberman 2000;Lilaonitkul and Guinan 2009), these approaches based on otoacoustic emissions (OAEs) do not provide a direct estimate of the decrease in OHC gain produced by the ipsilateral MOC pathway when elicited by sound Guinan 2006). examined the effects of the MOCR by presenting a sound contralateral to the measurement ear.…”
Section: Bmentioning
confidence: 99%